2011
DOI: 10.1186/1756-6614-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of PIN1 gene in papillary thyroid carcinoma

Abstract: BackgroundPeptidyl-prolyl cis/trans isomerase (Pin1), encoded by PIN1 gene with locus in chromosome 19p13, is an enzyme that catalytically induces conformational changes in proteins after phosphorylation on serine or threonine residues preceding proline (pSer/Thr-Pro motifs); in this way, it has an influence on protein interactions and intracellular localizations of proteins. The aim of the study were: 1) an assessment of PIN1 gene expression level in benign and malignant thyroid lesions; 2) the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the aforementioned reports, the authors suggest that the presence of mutations involving the RET/PTC oncogenes may be an early molecular indicator of papillary thyroid microcarcinoma lesions. Recent experience with the use of PCR in cytological diagnostic management of material obtained by FNAB may be of importance in detecting neoplastic lesions before they become clinically manifested [15]. The significance of molecular studies as an element of cytological diagnostics of thyroid lesions is confirmed by considerable differences in papillary thyroid cancer diagnoses in biopsy materials.…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned reports, the authors suggest that the presence of mutations involving the RET/PTC oncogenes may be an early molecular indicator of papillary thyroid microcarcinoma lesions. Recent experience with the use of PCR in cytological diagnostic management of material obtained by FNAB may be of importance in detecting neoplastic lesions before they become clinically manifested [15]. The significance of molecular studies as an element of cytological diagnostics of thyroid lesions is confirmed by considerable differences in papillary thyroid cancer diagnoses in biopsy materials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by the authors of the presented study suggested that an increased expression of cyclin D, Pin 1 (peptidyl-prolyl cis/trans isomerase, which also plays a critical role in cell restriction points -particular in G1/S phase) and cyclin E, could play an important role in PTC carcinogenesis [11,12,13,14]. However, the role of other cell cycle regulatory proteins in PTC remains largely undefined.…”
Section: Discussionmentioning
confidence: 88%
“…Previous researches have rarely been done to investigate the relationship between Pin1 and papillary thyroid carcinomas (PTCs); Masahiro et al [ 21 ] confirmed Pin1 mRNA expression in PTC by RT-PCR in their investigation, and they pointed out that Pin1 immunoreactivity was significantly higher in PTC than in follicular adenomas (FAs), the same with Andrzej et al study [ 22 ]. In our study, we investigated whether the expression pattern of Pin1 was different in distinct PTC stage.…”
Section: Introductionmentioning
confidence: 76%